2005
DOI: 10.1093/jjco/hyi145
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life after Radical Prostatectomy in Japanese Men: 2 year Longitudinal Study

Abstract: Despite reports of problems with sexuality and urinary continence, general HRQOL was mostly unaffected by RP after 6 months. RP had a favorable impact on mental health. Although urinary function did not completely return to the baseline level even at 2 years after RP, recovery from urinary bother was rapid. RP had serious consequences on libido, erectile function and sexual activity. In the second year, the sexual function of those who underwent RP with bilateral nerve sparing procedure continued to improve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 27 publications
1
16
1
Order By: Relevance
“…The questionnaire submission rates among these patients were 95%, 97%, 100%, 91%, 99%, 100%, 91% and 87% at 3,6,12,18,24,36,48 and 60 months after treatment, respectively. The mean HRQOL scores are shown in Figure 1 (general scales).…”
Section: General Hrqol Assessmentmentioning
confidence: 91%
See 2 more Smart Citations
“…The questionnaire submission rates among these patients were 95%, 97%, 100%, 91%, 99%, 100%, 91% and 87% at 3,6,12,18,24,36,48 and 60 months after treatment, respectively. The mean HRQOL scores are shown in Figure 1 (general scales).…”
Section: General Hrqol Assessmentmentioning
confidence: 91%
“…There were no treatment-related deaths. Only patients with preoperative HRQOL data and data from at least two later times (3,6,12,18,24,36,48 or 60 months after surgery) were included in the analysis, resulting in a final study cohort of 143 subjects. Table 1 lists the selected demographic and clinical characteristics of the study sample.…”
Section: Background Characteristics Of the Study Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…LUTSs after RP gradually improve, reaching a plateau at about 6 months. 7,8 We therefore excluded 3 patients who underwent MRI <6 months after RP, as these patients were assumed to still be undergoing improvement of LUTS. All patients underwent preoperative MRI.…”
Section: Patients and Methods Patientsmentioning
confidence: 99%
“…The duration between RP and performance of postoperative MRI was also inconsistent. Namiki et al 7,8 reported that LUTS gradually improves after RP, plateauing after about 6 months. Because the present study excluded those patients who underwent MRI within 6 months after RP, no correlation between duration until postoperative MRI and LUTS was observed.…”
Section: Commentmentioning
confidence: 99%